Synthesis and Antimicrobial Properties Pectin + CuNi Films and Characterization by Scanning Electron Microscopy - Illanez, Yamila; Cangiano, Corina; Lambrese, Yesica Sabrina; Fernandez, Cecilia; Esquivel, Marcelo Ricardo; Cangiano, Maria de los Ángeles (New Environmentally-Friendly Materials, 2025)
The synthesis of pectin-based films containing nanoparticles of CuNi (NPs), with potential antimicrobial properties, as an active solid is presented in this work. The NPs were dispersed in pure pectin to be used as food packaging in the food industry. The samples obtained were laid flat to characterize the sample thickness. The goal of this work is to find appropriate electron microscopy techniques to characterize the dispersion of the NPs on the pectin film and the pectin microstructural and antimicrobial characteristics properly. Different microstructural techniques of scanning electron microscopy modes were used to study the films, including low-voltage scanning electron microscopy (SEM) and low-voltage energy-dispersive spectroscopy (EDS). The condition of low beam voltage allows the sample characterization without destroying the sample surface/bulk due to electron irradiation. The pectin films containing raw NPs (pectin + NPs) and milled NPs (pectin + milled NPs) were observed by SEM in two different image modes: secondary electrons (SE) and backscattered electrons (BSE). The last mode allows the identification of sample components, i.e., matrix + samples containing different atomic Z numbers. This fact allows us to know the distribution of the metal particles within the volume of the sample. The results obtained in this work are relevant for the characterization and further use of these films in the protection of snacks in the food industry.